Partisipasi Siswa Dalam Meningkatkan Mutu Pembelajaran Pendidikan Islam - Nor kamalia (PT Barkah Ilmi Fiddunya, 2024)
This study aims to explore how student participation can affect the enhancement of Islamic education quality in schools. Student involvement in the teaching and learning process is a critical factor that can improve overall educational quality. Using a qualitative approach, this research gathers data from library studies. The results indicate that active student participation in discussions, question-and-answer sessions, and group activities significantly contributes to the understanding and application of the lesson material. Students who are engaged in the learning process not only demonstrate a better understanding of Islamic concepts but also show increased motivation to participate in religious and social activities outside the classroom. Additionally, teachers who implement teaching strategies that encourage student participation, such as project-based learning methods, observe improved outcomes. In conclusion, student participation is a key element in enhancing the quality of Islamic education. To achieve optimal results, it is crucial for educators to create a supportive learning environment that fosters active student involvement. This study suggests that curriculum development and teaching methods in Islamic education should consider strategies that can enhance student participation as a means to improve quality